Technology in Art Therapy: Ethical Challenges. - Alders, Amanda; Beck, Liz; Allen, PatB.; Mosinski, Barbara"Basia" (Art Therapy: Journal of the American Art Therapy Association, 2011)
As technology advances, art therapy practices are adapting to the demands of a new cultural climate. Art therapists face a number of ethical challenges as they interact with increasingly diverse populations and employ new media. This article addresses some of the ethical and professional issues related to the use of technology in clinical settings. Specific areas of the American Art Therapy Association's ethical guidelines are discussed with respect to the uses of technology in art therapy practice.